2015
DOI: 10.1016/j.jviromet.2015.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Droplet Digital PCR from RNA and DNA extracts with direct comparison to RT-qPCR: Clinical implications for quantification of Oseltamivir-resistant subpopulations

Abstract: The recent introduction of Droplet Digital PCR (ddPCR) has provided researchers with a tool that permits direct quantification of nucleic acids from a wide range of samples with increased precision and sensitivity versus RT-qPCR. The sample interdependence of RT-qPCR stemming from the measurement of Cq and ΔCq values is eliminated with ddPCR which provides an independent measure of the absolute nucleic acid concentration for each sample without standard curves thereby reducing inter-well and inter-plate variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 28 publications
2
109
0
Order By: Relevance
“…For CMV, Hayden et al [12] and Sedlak et al [47] found a higher precision at high CMV concentrations, although equal precision was found for lower levels of CMV. Similar findings have been reported for hepatitis C virus (HCV) [29], HBV [20] and influenza [30].…”
Section: Increased Precisionsupporting
confidence: 83%
See 2 more Smart Citations
“…For CMV, Hayden et al [12] and Sedlak et al [47] found a higher precision at high CMV concentrations, although equal precision was found for lower levels of CMV. Similar findings have been reported for hepatitis C virus (HCV) [29], HBV [20] and influenza [30].…”
Section: Increased Precisionsupporting
confidence: 83%
“…This dPCR approach may apply well in the setting of virology because emerging drug resistance mutations also need to be screened/monitored. In this context, a small number of papers have already explored this possibility, indicating that dPCR is more sensitive, compared with qPCR, at detecting low levels of emerging drug-resistant mutations [29][30][31]. Alternatively, dPCR can also be used for comparing the ratio of viral sequences to the number of haploid cellular genomes.…”
Section: Applications Of Digital Polymerase Chain Reaction (Dpcr) In mentioning
confidence: 99%
See 1 more Smart Citation
“…A single reaction mix was therefore produced for each sample and for all experiments which was split (20 µL each) for data acquisition between platforms (see Materials and Methods) as similarly designed in a previous study 13 . Since qPCR is a sample interdependent technology where the relative quantity and normalized gene expression data rely on ΔCq values, the analysis from a single plate assures the best quality results by eliminating any bias from inter-plate variability 16, 17 .…”
Section: Resultsmentioning
confidence: 99%
“…However, there are two distinct differences: 1) the partitioning of the PCR reaction into thousands of individual reaction vessels prior to amplification and 2) the acquisition of data at reaction end point. These factors offer the advantage of direct and independent quantification of DNA without standard curves giving more precise and reproducible data versus qPCR especially in the presence of sample contaminants that can partially inhibit Taq polymerase and/or primer annealing 1113 . In addition, end-point measurement enables nucleic acid quantitation independently of the reaction efficiency, resulting in a positive-negative call for every droplet and greater amenability to multiplexed detection of target molecules 14 .…”
Section: Introductionmentioning
confidence: 99%